(untitled) (Bangladesh Agronomy Journal, 2015)
An experiment was carried out in the field laboratory at the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh, during rabi season of 2009-2010. Planting material was maize var. BARI hybrid maize 7.Three levels of population density (66667, 83333 and 111111 plants ha-1) and four source-sink manipulation, viz. removed all leaf blades below the lower most cob, removed tassel and all leaf blades below the lower most cob, removed all leaf blades except those adjacent to cob and no clipping, were imposed at silking stage. During crop growth, removal of all leaf blades below the cob showed less adverse effect on grain yield and yield parameters and the leaves so removed can be used as green fodder. Removal of tassel and all leaf blades except those adjacent to cob showed adverse effect on grain yield and yield parameters. Complete defoliation severely reduced grains on cob. The highest gross return and benefit cost ratio (BCR) was obtained from the treatment having 1,11,111 plants ha-1 with no clipping while the lowest from the treatment with removal of all leaf blades excluding those adjacent to cob in 66667 plants ha-1. In case of dual purpose, 1,11,111 plants ha-1 with removal of tassel and all leaf blades below the lower most cob gave the highest gross return but 66667 plants ha-1 with removal of all leaf blades below the lower most cob gave the highest BCR (1.78) Bangladesh Agron. J. 2014, 17(1): 59-66